The effect of therapeutic alliance on attitudes toward psychiatric medications in schizophrenia - Lim, Madeline (2022)
Purpose/Background: The differential influence of therapeutic alliance with different health care professionals on patients' medication adherence has never been examined. Methods/Procedures: Ninety-five stable outpatients (91 patients with schizophrenia and 4 patients with schizoaffective disorder) were recruited. Individual, clinical, and medication factors were assessed, along with drug attitude (10-item Drug Attitude Inventory). Comparison on these factors was made between outpatients who identified psychiatrists as the health care professional most involved in their care, as compared with other health care professionals. Findings/Results: Older age, longer duration of illness, presence of medical comorbidities, lower levels of internalized stigma, higher levels of insight, higher levels of functioning, lesser severity of depressive symptoms, and positive symptoms were found to be significantly associated with greater levels of drug attitude (small to moderate associations). Only therapeutic alliance had a large correlation with drug attitude (ρ = 0.503, P < 0.001). The therapeutic alliance scores between the 2 health care professionals groups are not significantly different. However, participants who have identified psychiatrists as the health care professional that contributed the most to their recovery reported a significantly more positive attitude (μ = 6.18, SD = 3.42) toward psychiatric medication as compared with the other health care professionals group (μ = 3.11, SD = 5.32, P = 0.004). Only 2 factors, the Revised Helping Alliance Questionnaire (β = 0.424, P < 0.001) and Personal and Social Performance scale (β = 0.272, P = 0.006), were statistically significant predictors of drug attitude. Implications/Conclusions: Therapeutic alliance is found to be the lead factor associated with drug attitude in patients with schizophrenia. Identifying psychiatrists as the health care professional most involved in the patients' recovery can greatly increase patients' drug attitudes. Maintaining individuals' functioning also contributes to drug attitude.